ELECTRON MICROSCOPE STUDIES ON THE SURFACE COAT OF THE NEPHRON - Groniowski, J. (The Rockefeller University Press, 1969)
Attempts to make visible the carbohydrate coat at the free cell surface of glomeruli as well as the tubules of rabbit kidney were undertaken. The ruthenium red procedure was performed, according to Luft, at various pH values. Moreover, the colloidal iron and the colloidal thorium methods were used. Neuraminidase digestion was also performed. In the ruthenium red procedure the luminal face of the epithelial cells of the nephron was coated distinctly with reaction product. The results obtained revealed that some of the differences at various levels of the nephron depended on the pH values. In glomeruli and proximal convoluted tubules the optimum pH value was 7.4; in the ascending limb of Henle loops and distal convoluted tubules the optimum pH value was 6.8. The ruthenium red-positive surface coat was either closely connected with, or appeared as a part of, the outer leaflet of the unit membrane. The slit pores of glomeruli were also covered by a coat continuous with the surface coat of the adjacent foot processes. The coat lining the microvilli of proximal convoluted tubules completely filled the intervillous spaces. Also, both the colloidal iron method and the colloidal thorium method evidenced the presence of surface coat. Pre-treatment with neuraminidase abolished the effect of the Hale reaction. These results may indicate that the surface coat of the epithelia of the nephron shows the presence of glycoproteins containing siliac acid residues.